What drives consumer participation in virtual CSR? The impact of external scenarios - Fan Yang; Yuting Song; Jinyi Hu; Huiying Zhang (PLoS ONE, 2026)
The proliferation of social media has transformed the fulfillment of corporate social responsibility (CSR) from traditional offline activities to emerging online methods, ushering in the era of Virtual CSR activities. This study focuses on the crucial issue of enhancing consumer engagement in Virtual CSR initiatives. Drawing upon the Theory of Planned Behavior and Perceived Risk Theory, this study empirically analyzes the factors influencing consumers’ willingness and behavior to participate in Virtual CSR activities through questionnaire surveys. Our findings reveal that behavioral attitudes, perceived behavioral control, and external scenarios positively impact consumer willingness to participate, which in turn significantly promotes participation behavior. Furthermore, willingness to participate serves as a mediator between these factors and actual participation behavior. Based on these insights, we propose practical recommendations for enterprises to optimize their Virtual CSR strategies.